Recent progress in flow‐induced polymer crystallization. Issue 23 (15th September 2022) - Nie, Cui; Peng, Fan; Cao, Renkuan; Cui, Kunpeng; Sheng, Junfang; Chen, Wei; Li, Liangbin
Abstract: During industrial processing, such as film blowing and injection molding, semicrystalline polymers have to be subjected to external flow. Flow changes the nucleation rate, crystal morphology and polymorphism of polymers. As flow can be tunable, polymeric products with different macroscopic performance and versatile applications can be obtained. Understanding polymer crystallization with the presence of flow, or namely flow‐induced crystallization (FIC), is crucial to optimize polymer processing parameters and to understand phase transition under far‐from equilibrium conditions, as FIC is essentially a typical nonequilibrium process. Current review aims to summarizes recent achievements of FIC during last five years from three aspects: theory, experiment and simulation. First, we present the FIC model and theory, including the classical conformational entropy reduction model, the newly developed POLYdisperse STRain Accelerated Nucleation Dynamics (PolySTRAND) Model and uFIC Model. Then we discuss the FIC experiments under both well‐controlled flow and complex processing conditions. Finally, we show the recent advance of FIC in computer simulation. With the fast development in modeling efficiency, more detailed nucleation and structure transition processes during FIC can be obtained, which promote the study of molecular mechanisms of FIC. Abstract :